Studi Potensi Ekonomi SUB Sektor Pariwisata Religi Terhadap PAD Kabupaten Bangkalan: Pendekatan Prediksi Panel - Faizal Amir; Elfira Maya Adiba (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
From year to year, the halal industry trend is increasing in demand. This is caused by consumer trust in halal products. Halal products are increasingly popular because they guarantee cleanliness and safety in their use. Halal products are not only in the financial sector, but more than that, including halal food, halal cosmetics, sharia tourism or halal tourism, and so on. This research aims to determine the effect of government spending, hotel occupancy rates, tax revenues, labor force participation rates, number of tourists, and consumption on Regional GDP per capita. This research uses secondary data obtained from BPS Bangkalan Regency. The data analysis technique uses the common effect model (CEM) as part of panel data. Based on the results of data processing, it was found that hotel occupancy rates, tax revenues, labor force participation rates, number of tourists and consumption had a positive and significant effect on Regional GDP per capita of Bangkalan Regency. The government expenditure variable has a positive relationship, but has no significant effect on the Regional GDP of Bangkalan Regency.